Medical management of metastatic medullary thyroid cancer. Issue 21 (18th June 2014) - Maxwell, Jessica E.; Sherman, Scott K.; O'Dorisio, Thomas M.; Howe, James R.
<x xml:space="preserve">Abstract</x> Medullary thyroid cancer (MTC) is an aggressive form of thyroid cancer that occurs in both heritable and sporadic forms. Discovery that mutations in the rearranged during transfection (RET) proto‐oncogene predispose to familial cases of this disease has allowed for presymptomatic identification of gene carriers and prophylactic surgery to improve the prognosis of these patients. A significant number of patients with the sporadic type of MTC and even those with familial disease still present with lymph node or distant metastases, making surgical cure difficult. Over the past several decades, many different types of therapy for metastatic disease have been attempted with limited success. Improved understanding of the molecular defects and pathways involved in both familial and sporadic MTC has resulted in new hope for these patients with the development of drugs targeting the specific alterations responsible. This new era of targeted therapy with kinase inhibitors represents a significant step forward from previous trials of chemotherapy, radiotherapy, and hormone therapy. Although much progress has been made, additional agents and strategies are needed to achieve durable, long‐term responses in patients with metastatic MTC. This article reviews the history and results of medical management for metastatic MTC from the early 1970s up until the present day. Cancer 2014;120:3287–3301. © 2014 American Cancer Society.